The Effect of Differentiated Instruction Strategy on the Academic Achievement of First Intermediate Grade Students in the Subject of Reading - جاسم, ايناس وليد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study investigates the effectiveness of differentiated education as strategies to improve the academic achievement of reading for first-grade intermediate students in Iraq, Babylon. The study sample consisted of 60 students and was divided into a control group and an experimental group. The researcher followed the teaching strategies combining the flexible, tiered learning house in the areas of content, process and product to teach the experimental group. The traditional method that suits everyone was followed when teaching the control group. The results indicated that the employment of differentiated education practically contributed to improving students' achievement in their reading achievement for the subject matter, where the experimental group was statistically superior to the control group. The results showed that differentiated education had an effect on academic achievement. The current study aims to describe the impact of differentiated education on the academic achievement of first-grade intermediate students (low achievers and outstanding). Taking into account the teacher's time and effort. In order to obtain the data, the pre-test and the post-test were used as a tool to measure the decline or progress of students’ performance. The experimental group was able to improve its scores from the pre-test to the post-test. Therefore, the results revealed a significant improvement in the grades obtained by students after applying differentiated education. This is evidence of differentiated instruction as a strategy that has a significant impact on students' academic achievement.